2019
DOI: 10.1039/c9nr02463h
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin-based metal–organic frameworks: protonation induced Q band absorption

Abstract: In this work, porphyrin-based MOF nanosheets were formulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
5
41
0
Order By: Relevance
“…When using hollow CoO/Co 2 Mo 3 O 8 as electrode material ( Figure S10a, Supporting Information), in addition to the formation of SEI, the initial reduction peaks can be attributed to the reduction of Co 2 Mo 3 O 8 (Equation (2)) and CoO (Equation (3)) accompanying with nonnegligible capacity fading. [40,41] After two cycles, the shapes of CV plots maintained unchanged, and Co 0 and Mo 0 metal nanoparticles were oxidized to their corresponding metal oxides of CoO and MoO 2 , respectively, according to Equations (4) and (5). [34,42] This is in good accordance with that observed in GCD plots in Figure S10b (Supporting Information), where a rapid capacity loss was observed and eventually maintained at 140 mAh g −1 after 500 cycles due to their poor crystallinity, low conductivity, and severe volume change resulting in invalid contact between active materials and current collectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When using hollow CoO/Co 2 Mo 3 O 8 as electrode material ( Figure S10a, Supporting Information), in addition to the formation of SEI, the initial reduction peaks can be attributed to the reduction of Co 2 Mo 3 O 8 (Equation (2)) and CoO (Equation (3)) accompanying with nonnegligible capacity fading. [40,41] After two cycles, the shapes of CV plots maintained unchanged, and Co 0 and Mo 0 metal nanoparticles were oxidized to their corresponding metal oxides of CoO and MoO 2 , respectively, according to Equations (4) and (5). [34,42] This is in good accordance with that observed in GCD plots in Figure S10b (Supporting Information), where a rapid capacity loss was observed and eventually maintained at 140 mAh g −1 after 500 cycles due to their poor crystallinity, low conductivity, and severe volume change resulting in invalid contact between active materials and current collectors.…”
Section: Resultsmentioning
confidence: 99%
“…[2,3] Owing to their high surfaceto-volume ratio, fast charge transport, and shortened ion diffusion pathway, which are beneficial for electrochemical kinetics, 2D materials are considered as superior electrode candidates for energy storage. [4][5][6] In particular, MXene (e.g., Ti 3 C 2 T x ) as an essential member of 2D materials shows additional merits of metallic conductivity, low diffusion barrier for lithium ions, and ignorable volume change during intercalation/de-intercalation process. [7] Nevertheless, the application of MXene in LIBs…”
Section: Introductionmentioning
confidence: 99%
“…With increasing TFSA, the absorption peak at 420 nm decreases Page 5 of 19 CCS Chemistry while the peak at 446 nm increases, consistent with the spectra variation tendency of the porphyrin monomer, in which the porphyrin skeletons were gradually charged with protons. [20] Similarly, for the TPCP structure, the spectra indicate that the proton-exfoliated TPCP was obtained. The protonation process follows the principle of the lowest energy, which starts at the surface of the TPCP without solubility at low TFSA molar ratios.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, we hypothesize that the protonation and solubility start at the surface and the soluble mechanism is due to the colloidal property with surface charged TPCP solutions (Figure 3). [20] Moreover, we propose that the proton density of the TPCP surface at the TFSA molar ratio of 3.8% results in the lowest density of soluble property. With the TFSA concentration further increasing, the proton density of the TPCP surface is enhanced, which represents a positive correlation between the protonation and solubility.…”
Section: Resultsmentioning
confidence: 91%
“…And with the ratio of Co 2+ increased, there was a small redshift on the Soret peak (434 nm) while four peaks in Q region gradually merged to one hump peak at ≈540 nm (Figure 2d), which strongly indicated that the pyrrolic N could not be coordinated when the sole Ce 3+ coordinate with the TCPP, however, with the attendance of Co 2+ the pyrrolic N gradually occupied by the Co 2+ . [51,52] The X-ray photoelectronic spectroscopy (XPS) was also conducted to reveal the changes in the elements during the assembling process. The survey spectra of the MOFs showed the Ce and Co successfully coordinated with the ligand (Figure S2, Supporting Information).…”
Section: Assembly and Characterizationsmentioning
confidence: 99%